Analysis of basic shooting technique abilities in soccer games - Rusli, Muhammad; Jud, Jud; Marsuna, Marsuna (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
This study was conducted for several reasons. Some students have bad experiences understanding and applying the correct basic shooting techniques. Moreover, a lack of adequate practice or understanding of the technique can cause it. Besides, students have trouble maintaining consistency when implementing basic shooting techniques. Some factors, such as physical fatigue, lack of concentration, or lack of regular exercise, can cause it. Thus, this research aimed to analyze basic shooting technical abilities in soccer games. This research applied quantitative research involving 30 high school students actively participating in extracurricular activities as the research participants. The instrument was the shooting test. The data analysis technique used descriptive statistics entered predetermined categories. The categorization was grouped into 5: excellent, good, fair, poor, and very poor. Then, the data were entered into the data processing technique in percentages. The results show that students’ basic shooting technical abilities were in a good category, with a percentage of 40%, and the lowest is 3%. From the results of research on basic skills in soccer shooting techniques, several main points were concluded, namely that from the sample size, most students (53%) were still in the category of basic skills in good shooting techniques. Students who fall into the poor and very poor categories need special attention and extra guidance to improve their abilities in basic shooting techniques.